Synthesis, structural and magnetic properties of pure and Li2+ doped NiO nanomaterial. (2022) - Subash, M.; Chandrasekar, M.; Inmozhi, C.; Gobi, G.; Saravanan, M.E. Raja; Uthrakumar, R.
Abstract: The present work used a simple sol–gel technique to manufacture undoped NiO and Li-doped Nickel Oxide (NiO) nanoparticles. XRD, FT-IR, SEM, EDAX, and VSM were used to characterise a NiO nanoparticle. NiO was shown to be in the monoclinic phase by XRD analysis. The Fourier transform infrared spectroscopy was employed to demonstrate the existence of a free Ni-O bond in NiO nanoparticles. The SEM examination revealed that the aggregated nanoparticles were not homogeneous in size. The EDAX was utilised to determine the element's composition. The magnetic characteristics of these nanoparticles were determined using a Vibrating Sample Magnetometer (VSM), confirming their ferromagnetic activity at room temperature.